The Drosophila Forkhead/Fox transcription factor Jumeau mediates specific cardiac progenitor cell divisions by regulating expression of the kinesin Nebbish - Andrew J. Kump (Nature Portfolio, 2021)
Abstract Forkhead (Fkh/Fox) domain transcription factors (TFs) mediate multiple cardiogenic processes in both mammals and Drosophila. We showed previously that the Drosophila Fox gene jumeau (jumu) controls three categories of cardiac progenitor cell division—asymmetric, symmetric, and cell division at an earlier stage—by regulating Polo kinase activity, and mediates the latter two categories in concert with the TF Myb. Those observations raised the question of whether other jumu-regulated genes also mediate all three categories of cardiac progenitor cell division or a subset thereof. By comparing microarray-based expression profiles of wild-type and jumu loss-of-function mesodermal cells, we identified nebbish (neb), a kinesin-encoding gene activated by jumu. Phenotypic analysis shows that neb is required for only two categories of jumu-regulated cardiac progenitor cell division: symmetric and cell division at an earlier stage. Synergistic genetic interactions between neb, jumu, Myb, and polo and the rescue of jumu mutations by ectopic cardiac mesoderm-specific expression of neb demonstrate that neb is an integral component of a jumu-regulated subnetwork mediating cardiac progenitor cell divisions. Our results emphasize the central role of Fox TFs in cardiogenesis and illustrate how a single TF can utilize different combinations of other regulators and downstream effectors to control distinct developmental processes.